2011
DOI: 10.1002/dmrr.1218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different protein content and glycaemic index of ad libitum diets on diabetes risk factors in overweight adults: the DIOGenes multicentre, randomized, dietary intervention trial

Abstract: Results: The LCD period was initiated by 932 adults, 773 were randomised to the 5 diets and 548 completed the intervention. The HP and LGI diets were related to weight-loss management and to a lower drop-out rate. The LP/HGI diet induced a greater increase in HOMA-IR during the 6 month period. The HP and LGI diets decreased HOMA-IR (p<0.001) in those patients with the highest weight-loss (≥10% of initial body-weight).The LGI diets also lead to a decrease in fructosamine levels (p<0.05), and plasma insulin resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Interestingly, no adverse effects accompanying the higher production of nitrogenous metabolites were diagnosed or measured in the DiOGenes participants [7], which concurs with an experiment comparing the intake of protein-enriched meal replacements instead of standard meal replacements recommended for weight management, where no detrimental effects on routine measures of liver function, renal function, or bone density at one year were reported [32]. In the DiOGenes trial, the diets with higher protein content were more acceptable than the LP diets [33], but a role for the concomitant reduction in carbohydrate content in such diets could not be disregarded [34]. Our results indicate that even a modest increase in protein intake (3-7%) was sufficient to minimize weight regain.…”
Section: Dietary Intervention and Delivery Modelsupporting
confidence: 67%
“…Interestingly, no adverse effects accompanying the higher production of nitrogenous metabolites were diagnosed or measured in the DiOGenes participants [7], which concurs with an experiment comparing the intake of protein-enriched meal replacements instead of standard meal replacements recommended for weight management, where no detrimental effects on routine measures of liver function, renal function, or bone density at one year were reported [32]. In the DiOGenes trial, the diets with higher protein content were more acceptable than the LP diets [33], but a role for the concomitant reduction in carbohydrate content in such diets could not be disregarded [34]. Our results indicate that even a modest increase in protein intake (3-7%) was sufficient to minimize weight regain.…”
Section: Dietary Intervention and Delivery Modelsupporting
confidence: 67%
“…In overweight but otherwise healthy subjects, a low energy diet (LED), defined as 800 – 1000 kcal/day, resulted in a considerable weight loss with no apparent risk [12]; however, there are no studies describing the use of LED in patients with CAD. The pan-European study DiOGenes used an LED to facilitate an initial weight loss of more than 8% of the original body weight in an overweight population, which resulted in a reduction of both cardiovascular [13] and metabolic risk [14]. A British study using a very low energy diet (600 kcal) to induce weight loss showed that insulin resistance and beta cell failure could be reversed in diabetic patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, glucose, free fatty acids (FFA) (automatic spectrophotometric enzymatic techniques) and insulin were measured from fasting samples [13]. Insulin concentrations were measured by a colorimetric assay (Ortho-Clinical Diagnostics, Johnson & Johnson, Birkerød, Denmark) [14]. Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) and insulin sensitivity (Matsuda index) were calculated.…”
Section: Anthropometry and Blood Samplingmentioning
confidence: 99%